Policiamento comunitário no amazonas: ações implementadas e a percepção dos atores envolvidos - Albuquerque, Lilibeth Cynthia Corrêa de (2008)
This paper aims to describe community policing, correlating with the actions implemented in the Amazon, and analyzing the perception of actors involved in public security system on this model. The national and international experience show that the adoption of this model requires structural changes, administrative and organizational. Community participation is a key feature of this model. The system of public security of Amazonas not yet fully adopts the Community model, despite appear in his project to revitalize procedures similar to the model, as interaction between civilian police and military installation of Interactive Community Councils of Public Security, although these are not regulated legally. An important factor in this process relates to perceptions of the actors involved in need take a broad view about the police action. The interviews with the actors involved in the system of public safety shows that the current model does not meet the expectations of society as both the institution. The community policing is seen as an alternative capable of assisting in improving the system.